Prisons in 19th century Colombia: a historiographical essay (Tzintzun, Revista de Estudios Históricos, 2021)
In this paper is presented a historiographic review, which looks into the prison system of the 19th century in Colombia. The historic literature of the last 30years concerning jails, â€œreclusion homesâ€ for adulterous and ex-prostitute women and prisons throughout the 19th century is included. This literature is approached through its themes, conclusions, sources and positions in the face of international developments on this area. Trends and general guidelines on the study of this historical phenomenon in Colombia are identified.
Keywords: prisons; Colombia; 19th Century, historiograph